Influence of location attributes on home buyers’ purchase decision - Mang, Jie Sheng; Zainal, Rozlin; Mat Radzuan, Indera Syahrul (ExcelingTech Pub, 2018)
Owning a home at a bad location is detrimental to its market value. Besides, demographic forces have influenced the demand for housing over the past decades. This study identifies the type of location attributes and demographic characteristics’ influences on housing purchase decisions of home buyers in Iskandar Malaysia. This research intends to collect data through questionnaire. The respondents are the house owners of Taman Nusa Sentral. The data is then analysed with correlation to study the relationship between demographic and location variables. Most of the demographic characteristics, except Gender and Income, have significant influences on location facilities and services when it comes to house purchase decision. This study is able to overcome the problems of low house owning rate and oversupply and provides preferable location attributes to the housing developers.